2020
DOI: 10.3390/ma13132939
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Viscosity and Yield Stress of Cement Grouts at True Ground Temperatures Based on the Flow Spread Test

Abstract: The rheology of cement grouts often plays a crucial role in the success of rock grouting. In practice, the rheological parameters should be timely adjusted according to the evolution of grouting pressure, flow rate and injection time. However, obtaining the magnitude of rheological parameters is not easy to achieve under site conditions. More importantly, the ground temperature in deep rock masses is elevated higher than that on the surface or under room conditions, which has been demonstrated to strongly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…However, the plastic viscosity increases to 153.8 cP at 2% vermiculite. A lower plastic viscosity of the cement slurry is recommended because its resistance to flow and pumping requirements are lower …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the plastic viscosity increases to 153.8 cP at 2% vermiculite. A lower plastic viscosity of the cement slurry is recommended because its resistance to flow and pumping requirements are lower …”
Section: Resultsmentioning
confidence: 99%
“…A lower plastic viscosity of the cement slurry is recommended because its resistance to flow and pumping requirements are lower. 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the dead weight and yield stress in the grout characteristics are primarily the components that significantly impact the process and degree of grouting diffusion decay. Numerous researchers have examined how time-varying viscosity affects the grouting process (Liang et al, 2022;Ma et al, 2023); additionally, time-varying grout yield stress has been observed (Xu et al, 2020;Nan et al, 2021); however, it is essential to note that the slurry is always in a flow state during the grouting process.…”
Section: The Concept Of Grouting Diffusion Decaymentioning
confidence: 99%
“…The development of deep engineering such as ultradeep drilling, deep laboratory, nuclear waste disposal, and deep resource mining had made temperature of rock increase from 30 °C at a depth of 800 m to 50 °C at a depth of 1500 m approximately [13][14][15][16][17]. In particular, the temperature of the rock had even exceeded 100 °C in some high-temperature tunnels such as Sichuan-Tibet Railway and EGS-E tunnel [18,19].…”
Section: Introductionmentioning
confidence: 99%